The Development and Validation of a Subjective Assessment Tool for the Hip in the Athletic Population. (September 2017) - Papaliodis, Dean N.; Banffy, Michael B.; Limpisvasti, Orr; Mohr, Karen; Mehran, Nima; Photopoulos, Christos D.; Kvitne, Ronald; ElAttrache, Neal S.
Background: No validated functional assessments are available that are designed specifically to evaluate the performance and function of the athletic hip. Subsections of some validated outcome assessments address recreation, but a full assessment dedicated to athletic hip function does not exist. Current hip scoring systems may not be sensitive to subtle changes in performance and function in an athletic, younger population. Hypothesis: The patient-athlete subjective scoring system developed in this study will be validated, reliable, and responsive in the evaluation of hip function in the athlete. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Based on the results of a pilot questionnaire administered to 18 athletic individuals, a final 10-item questionnaire was developed. Two hundred fifty competitive athletes from multiple sports completed the final questionnaire and 3 previously validated hip outcome assessments. Each athlete was self-assigned to 1 of 3 injury categories: (1) playing without hip/groin trouble; (2) playing, but with hip/groin trouble; and (3) not playing due to hip/groin trouble. The injury categories contained 196, 40, and 14 athletes, respectively. Correlations between the assessment scores and injury categories were measured. Responsiveness testing was performed in an additional group of 24 injured athletes, and their scores before and after intervention were compared. Results: The Kerlan-Jobe Orthopaedic Clinic (KJOC) Athletic Hip Score showed high correlation with the modified Harris Hip Score, the Nonarthritic Hip Score, and the International Hip Outcome Tool. The new score stratified athletes by injury category, demonstrated responsiveness and accuracy, and varied appropriately with improvements in injury category after treatment of injuries. Conclusion: The new KJOC Athletic Hip Score is valid, reliable, and responsive for evaluation of the hip in an athletic population. The results support its use for the functional assessment of the hip in future studies.